Diagnostic and Treatment Problems of Primary SclerosingCholangitis - Nurleili, Rezky Aulia; F, Intan Airlina; Lubis, Anna Mira (Jurnal Penyakit Dalam Indonesia, 2016)
Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease with high incidence reported in America (1/100.000 population), but there is still no data available in Indonesia. The best management of this disease is still not found. Thus, in this article author will discuss about the case of PSC in 49-years male patients hospitalized in Cipto Mangunkusumo hospital Jakarta and its treatment.